Reconciliation in Rwanda : perspectives from the parliament - Plath, Melissa (2010)
The purpose of this thesis is to examine the meaning of political reconciliation in Rwanda and the ways this is expressed. Thus, Rwandan Senators were interviewed to understand their interpretations of reconciliation in Rwanda. Furthermore, it seeks to understand the tools of reconciliation used in Rwanda and how Senators feel these contribute to the reconciliation process. This study attempts to understand the political through the personal.